Design, Synthesis, Cytotoxic Activity And DNA Intercalation Of New β-Carboline Derivatives - Mohideen, Mazlin (2018)
The focus of this study has been to investigate the in vitro cytotoxic effects of new β-carboline derivatives on the K562 human cancer cell line. Analysis using 3D-QSAR models has revealed the importance of derivatisation at position-2 and -9 of the β-carbolines. Two new series of N2-benzylated-β-carboline (M23-M46) and N2-N9-benzylated-1-substituted-β-carboline derivatives (M47-M113) were synthesised and characterised using four-step reaction and were produced in good yields (>70%). Compounds M23-M113 exhibited the most potent anticancer activity with IC50 values between 0.01-4 μM, except for compounds M88-M90 which produced IC50 values of more than 100 μM.